2006
DOI: 10.1002/ajh.20722
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in children affected by sickle‐cell disease and their parents

Abstract: Children affected with sickle-cell disease experience painful crises that may be life threatening, or felt as if they were. We evaluated by semistructured interviews and questionnaires the presence of posttraumatic stress disorder in 11 children affected by sickle-cell disease and having suffered at least one hospitalization for a painful crisis, and in their parents (10 mothers, 1 father). Three children (27%) and four parents (40%) were diagnosed with the disorder. It was not correlated to the disease severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
(6 reference statements)
1
20
1
1
Order By: Relevance
“…Several studies found that 30-40% of the caregivers had symptoms of psychological distress. [10][11][12][13] These studies were descriptive and did not compare caregivers of SCD patients to a control group of parents with healthy children. In order to conclude that psychological distress is related to caring for children with SCD, a well-matched control group is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that 30-40% of the caregivers had symptoms of psychological distress. [10][11][12][13] These studies were descriptive and did not compare caregivers of SCD patients to a control group of parents with healthy children. In order to conclude that psychological distress is related to caring for children with SCD, a well-matched control group is essential.…”
Section: Introductionmentioning
confidence: 99%
“…5 Mutations in genes which regulate the response to hypoxia, such as VHL and PHD2 and HIF-2α have recently been found in a number of familial polycythemia syndromes with high serum erythropoietin levels. 6,7 Familial thrombocytosis without involvement of other lineages can be caused by mutations in THPO or MPL. Some families with elevated serum thrombopoietin levels carry activating mutations in the THPO gene which cause overproduction of the thrombopoietin protein by a mechanism of increased translational efficiency for the mutant THPO mRNA.…”
Section: Jak2-v617fmentioning
confidence: 99%
“…Families and patients may experience post-traumatic stress disorder, the rate of occurrence of which is not correlated with disease severity. 6 Thus, the disease itself, independently of the number of hospital admissions and complications, adversely affects the quality of life of the patients and their families. This quality-oflife burden is being increasingly recognized by physicians and families as a key component in the risk/benefit ratio of treatments for SCD.…”
mentioning
confidence: 99%
“…Identifying anxiety in adolescents with SCD imposes a high clinical relevance, because of the distress stemming from anxiety itself, which may disturb the child's development, and fear of recurrence that may worsen the consequences of vaso-occlusion, and promote inadequate use of analgesics (Hofmann et al 2007). …”
Section: Examined 84 Nigerianmentioning
confidence: 99%